Microbiological Quality and Genotypic Speciation of Heterotrophic Bacteria Isolated from Potable Water Stored in Household Tanks - Tokajian, Sima (2004)
Upon storage, a statistically significant increase in heterotrophic plate count (HPC) was detected in samples from household tanks. The most consistent correlate of regrowth was found to be storage time, however, temperature and the microbiological quality of the influent water were also important. Total and fecal coliforms were detected in the influent water and in the household storage tanks. Coliforms growing at 37ºC were a small but significant part (about 0.002%) of the total heterotrophic population. In the influent, 92% of the coliforms (11 colony forming units/100 mL) at 44ºC were Escherichia coli, while in the household tanks it was 86%. The majority of isolates from the influent and the household tanks recovered on R2A agar formed pigmented colonies and were Gram-negative belonging to the α-, β-, and γ-subclasses of Proteobacteria. Overall, the α-subclass was the dominant type representing 61% of the recovered HPC, and 40 to 50% of the organisms based on 16S rDNA sequence analysis were members of the family Sphingomonadaceae. The presence of E. coli and the isolation of opportunistic pathogens as a significant part of the HPC population from both influent and household tanks indicated a potential health hazard to consumers.